Colonization of Helicobacter pylori in the oral cavity – an endless controversy?. (3rd September 2021) - Mao, Xiaojun; Jakubovics, Nicholas S.; Bächle, Maria; Buchalla, Wolfgang; Hiller, Karl-Anton; Maisch, Tim; Hellwig, Elmar; Kirschneck, Christian; Gessner, André; Al-Ahmad, Ali; Cieplik, Fabian
Abstract: Helicobacter pylori is associated with chronic gastritis, gastric or duodenal ulcers, and gastric cancer. Since the oral cavity is the entry port and the first component of the gastrointestinal system, the oral cavity has been discussed as a potential reservoir of H. pylori . Accordingly, a potential oral-oral transmission route of H. pylori raises the question concerning whether close contact such as kissing or sharing a meal can cause the transmission of H. pylori . Therefore, this topic has been investigated in many studies, applying different techniques for detection of H. pylori from oral samples, i.e. molecular techniques, immunological or biochemical methods and traditional culture techniques. While molecular, immunological or biochemical methods usually yield high detection rates, there is no definitive evidence that H. pylori has ever been isolated from the oral cavity. The specificity of those methods may be limited due to potential cross-reactivity, especially with H. pylori -like microorganisms such as Campylobacter spp. Furthermore, the influence of gastroesophageal reflux has not been investigated so far. This review aims to summarize and critically discuss previous studies investigating the potential colonization of H. pylori in the oral cavity and suggest novel research directions for targeting this critical research question.